Effect of Prolonged Moderate Exercise on the Changes of Nonneuronal Cells in Early Myocardial Infarction. (22nd July 2015) - Rinaldi, Barbara; Guida, Francesca; Furiano, Anna; Donniacuo, Maria; Luongo, Livio; Gritti, Giulia; Urbanek, Konrad; Messina, Giovanni; Maione, Sabatino; Rossi, Francesco; de Novellis, Vito
Abstract : Myocardial infarction (MI) is one of the leading causes of death in developed countries and it is characterized by several associated symptomatologies and poor quality of life. Recent data showed a possible interaction between infarction and brain inflammation and activity. Previous studies have demonstrated the beneficial effect of exercise training on deterioration in cardiac function after MI. In this study we analyzed in sedentary and trained rats the microglia and astrocytes 48 hours after MI in PVN, thalamus, prefrontal cortex, and hippocampus through immunofluorescence approach. We found significant changes in specific microglia phenotypes in the brain areas analyzed together with astrocytes activation. Prolonged exercise normalized these morphological changes of microglia and astrocytes in the prefrontal cortex, hippocampus, and thalamus but not in the PVN. Our data suggest that there is an early brain reaction to myocardial infarction induction, involving nonneuronal cells, that is attenuated by the prolonged exercise.